Analisis Manajemen Risiko di CV Ladang Management Menggunakan Model House of Risk (HOR) - Teguh Oktiarso; Immanuel Nathaniel Ondang; Sunday Noya (Teknik Industri Universitas Ma Chung, 2022)
Risk management is crucial to minimize the negative effects of potential risks on business processes and operations. In this study, CV Ladang Management, an individual bussiness in the advertising industry, implemented the House of Risk model to identify risk agents and develop appropriate mitigation plans. The analysis of data obtained through this model revealed 15 risk events and 15 risk agents that can affect the company's business processes. Based on the prioritization of risks, 7 priority risk agents were identified, and 11 mitigation plans were proposed to address them. The plans include measures such as choosing tailors with optimal distances and investing in sewing machines for each tailor. By implementing these mitigation plans, CV Ladang Management can reduce the impact of potential risks and ensure the continuity of its business operations.